Compact three‐way Gysel power divider with arbitrary power dividing ratio. Issue 15 (30th October 2020) - Chen, Haidong; Li, Hongping; Xue, Quan; Che, Wenquan
Abstract : This study proposes a compact structure of the three‐way Gysel power divider with arbitrary power dividing ratio, which has a significant difference from existing N ‐way ones with a common node in the centre of the circuit. First, existing equations are reviewed, and new analytical closed‐form equations are derived according to the proposed structure. The frequency bandwidths, affected by the parameters of isolation networks are investigated in detail and optimised for performance balance. For verification, the proposed three‐way Gysel power dividers are calculated, optimised and fabricated at the centre frequency of 3.5GHz with different dividing ratios of 1:1:1 and 1:2:3, respectively. Moreover, the equations are derived to design the N ‐way Gysel power divider.